The Effects of Market Structure and Competition Policy on Consumer Welfare and Economic Efficiency - Rashied, Ahmed Saeed; Obaid , Siham Abd Ali; Baban, Omar; Muhsin, Aseel Ibraheem (Journal of Ecohumanism, 2024)
Background: The complex relationship between market structure and competition regulation substantially impacts the functioning of contemporary economies. Comprehending this connection is crucial for evaluating how changes in market structures influence the effectiveness of competition rules, therefore impacting consumer well-being and overall market efficiency. Objective: This research seeks to investigate how various market arrangements impact the implementation and efficacy of competition rules. The study aims to analyse how oligopolistic behaviours, monopolistic inclinations, and competitive market dynamics impact the development and execution of regulatory policies. Methodology: This study utilises a multimodal research strategy, combining case studies, theoretical modelling, and empirical investigation across different businesses. It utilises qualitative studies to examine strategic behaviours and policy interventions and quantitative approaches to assess market concentration and its effects on competition. Results: The findings show that market structures significantly impact the effectiveness of competition legislation. Because of their significant market influence, oligopolies often need specialised regulatory structures to prevent anti-competitive practices. Competitive markets are resilient with little government involvement, but monopolistic markets need strict rules to guarantee fair competition. Conclusion: The research emphasises the significance of matching policy interventions with the intricacies of particular market systems to improve their efficacy. It supports implementing adaptable legislation that can adjust to changing market circumstances, promoting a competitive environment that benefits consumer protection and market stability. Policymakers and regulators should adjust their tactics to fit the present market conditions to support fair competition, innovation, and economic efficiency while protecting consumer well-being and market stability.